Study of Linearly Chirped 1-Dimensional Bragg Gratings Using Confluent Hypergeometric Function - Ayi Bahtiar; Rustam Efendi Siregar (Jurnal Fisika dan Aplikasinya, 2008)
A finite one-dimensional, linearly Bragg grating with chirp parameter C and index modulation depth n1 or coupling constant / n1is considered for numerical analysis of its performances by converting its coupled equations into a confluent hypergeometric equation. The operational parameters considered for the analysis consist of the group delay, the reflectance (R), the reflectance ripple (RR), the reflectance bandwidth (BW) and the group delay ripple (GDR). It is shown that increasing C leads to decreasing GDR and increasing BWwhich are favorable to the device performance. However, the RR is relatively unaffected while R suffers from an undesirable diminution. On the other hand, increasing results in the enhancement of R and BW while reducing RR when is increased beyond a certain turning point. But these are attained at the expense on enlarged GDR. The results of this study clearly points to the need of compromising between C and for the optimal operation of the device.